Mitochondrial Quality Control Governed by Ubiquitin - Ravanelli, Sonia; den Brave, Fabian; Hoppe, Thorsten (Frontiers in Cell and Developmental Biology, 2020)
Mitochondria are essential organelles important for energy production, proliferation, and cell death. Biogenesis, homeostasis, and degradation of this organelle are tightly controlled to match cellular needs and counteract chronic stress conditions. Despite providing their own DNA, the vast majority of mitochondrial proteins are encoded in the nucleus, synthesized by cytosolic ribosomes, and subsequently imported into different mitochondrial compartments. The integrity of the mitochondrial proteome is permanently challenged by defects in folding, transport, and turnover of mitochondrial proteins. Therefore, damaged proteins are constantly sequestered from the outer mitochondrial membrane and targeted for proteasomal degradation in the cytosol via mitochondrial-associated degradation (MAD). Recent studies identified specialized quality control mechanisms important to decrease mislocalized proteins, which affect the mitochondrial import machinery. Interestingly, central factors of these ubiquitin-dependent pathways are shared with the ER-associated degradation (ERAD) machinery, indicating close collaboration between both tubular organelles. Here, we summarize recently described cellular stress response mechanisms, which are triggered by defects in mitochondrial protein import and quality control. Moreover, we discuss how ubiquitin-dependent degradation is integrated with cytosolic stress responses, particularly focused on the crosstalk between MAD and ERAD.